Penegakan Hukum Pidana Terhadap Pungutan Liar Di Wilayah Hukum Patumbak (Studi Kasus Di Polsek Patumbak) - Karonika Gurusinga; Rizkan Zulyadi; M. Yusrizal Adi Syaputra (Universitas Medan Area, 2023)
Illegal levies (pungli) are levy activities carried out by someone for personal gain by violating the rules. The purpose of this study is to find out the factors that cause extortion in the jurisdiction of patumbak. This study uses empirical juridical research regarding the enactment or implementation of a normative legal provision in the act of the occurrence of a certain law made in society. The nature of this research is descriptive analysis. The data used in this research is secondary data, namely data obtained from library research in the form of legal materials. Data collection techniques, namely literature and field. The results of the study show that the causes of extortion in the patumbak jurisdiction are due to internal factors that abuse position or authority resulting in an intention to violate legal norms (crime) because we know that crime arises as a result of opportunity. The main factors are economic factors, lack of jobs and minimal education that causes crimes to occur in society, causing damage to norms in social life.